Spatial-temporal evolution and peak prediction of embodied carbon emissions in China's interregional trade - Mo, Shu; Wang, Ting (Frontiers in Public Health, 2022)
The embodied carbon in inter-regional trade has a vital impact on the decomposition of carbon emission reduction responsibilities and the formulation of carbon emission reduction strategies. However, compared with the more abundant results on embodied carbon in international trade, few studies have investigated the spatial-temporal evolution pattern and peak prediction of embodied carbon emissions between regions in China. This study applies the multi-regional input-output approach to measure the embodied carbon in inter-regional trade generated by value-added transfer and analyzes the evolution of its spatial and temporal patterns. The existence of an environmental Kuznets curve model with embodied carbon emissions as the index of en-vironmental pollution in China is examined, and the time of the inflection point is calculated. The environmental Kuznets curve model is further divided into four stages, and a two-dimensional model of economic growth and embodied carbon emissions is proposed. The empirical results show that the embodied carbon in interregional trade in China has an overall upward trend in the time dimension and a distribution characteristic of high in the west & north and low in the east & south in the spatial dimension. The Environmental Kuznets curve, which takes the embodied carbon emissions as an indicator of environmental pollution, presents an inverted U shape, and the time required to reach the inflection point varies from region to region. Economic development cannot be cross-stage but can shorten the duration of high carbon emissions. The government should promote the development of differentiated carbon emission reduction policies in each region, build an inter-regional cooperative carbon emission reduction mechanism, promote the low-carbon development of foreign trade, and realize the internal cycle of China's green economy. This study provides a reference for the provinces to formulate scientific and reasonable carbon emission reduction policies to achieve high-quality development of inter-regional trade.